Production potential of lactating Red Chittagong cows due to improved feeding in small-scale dairy farm (Progressive Agriculture, 2018)
The aim of the experiment was to reveal the production potential of lactating Red Chittagong cows through improved feeding. To achieve the aim, the experiment was designed in a completely randomized design with three dietary treatment groups having ten Red Chittagong cows in each group for a period of six months. The cows were randomly allocated to three dietary treatment groups, i.e., T0, T1 and T2. The cows of T0 group received only farmers’ diet (63% of dry matter intake of cows according to ARC, 1995) without the supplementation, served as control. The cows of T1 group received farmers’ diet (63%) plus 25% supplementation of formulated concentrate diet for deficit of requirement of cows {(63 + 9.25) = 72.25% dry matter intake of cows according to ARC, 1995)} and T2 group received farmers’ diet (63%) plus formulated concentrate diet to meet 100% requirement of cows according to ARC (1995) {(63% + 37%) = 100%}. The average milk production of Red Chittagong cows of T0, T1 and T2 groups was 2.40, 3.27 and 4.82 kg per day, respectively. The milk fat, protein, solids not fat, total solids and ash were 4.30, 3.85, 9.02, 13.34 and 0.70; 4.75, 3.70, 8.97, 13.73 and 0.71; and 5.45, 3.56, 8.86, 14.30 and 0.72, g per 100g milk, respectively, for T0, T1 and T2 groups. Therefore, the farmers’ diet plus supplementation of formulated concentrate diet (FCD) to meet 100% requirement of cows was a better improved feeding system of lactating Red Chittagong cows to derive good performance.Progressive Agriculture 29 (2): 147-157, 2018